Skrining fitokimia ekstrak air dan ekstrak etanol 70% Propolis Trigona sp. asal Lombok Utara - Ananta, Muhammad Naufal Farras; Nuralyza, Imasayu; Solehah, Kurnia; Pratama, Iman Surya; Aini, Siti Rahmatul (Universitas Mataram, 2024)
Propolis Trigona sp. has many benefits closely related to the secondary metabolites contained therein. Previous research related to propolis screening of Trigona sp. from North Lombok has been carried out. Still, it has yet to be carried out in the maceration method (1:20 w/v) with 70% water and ethanol solvent to obtain a comparison of secondary metabolites between the two solvents. This study aims to identify the content of secondary metabolites in the water extract and 70% ethanol extract of propolis Trigona sp. from North Lombok. Propolis was macerated with water and 70% ethanol solvent. The viscous extract was identified for its physical characteristics, consistency, color, and chemical characteristics through phytochemical screening. The results of the phytochemical screening showed that the aqueous extract and 70% ethanol extract contained alkaloids, flavonoids, tannins, triterpenoids, and quinones. Both extracts showed negative saponin results.